A systematic review of digital innovation in Higher Education Institutions in developing countries - Wambua , Ruth Nthenya (African Journal of Education,Science and Technology (AJEST), 2024)
Among the United Nations’ sustainable development goals is quality education, to ensure inclusive and equitable education and promote lifelong learning opportunities for all. Ensuring that all men and women have equal access to high-quality, reasonably priced technical and vocational education, as well as university education, is one of the goals. Universities are Higher education institutions (HEIs), and they have continued to experience immense digital innovations thanks to Information and Communication Technology (ICT) infiltration and advancements. Along with this, the premise of this systematic literature review is that, although research on digital innovation is growing, few studies are available on its consequences in developing countries, specifically on higher education institutions. Further, there is a strong argument for comprehending the body of research on this topic, especially when considering learning and teaching, stakeholder involvement, and research as cornerstones of education that are still undergoing the digital revolution. Therefore, the purpose of this review is to synthesize existing knowledge about digital innovation in HEIs in developing nations and to suggest a research agenda based on updated theoretical thinking to fill in knowledge gaps. Peer-reviewed journal publications for the past ten (10) years (2013-2022) were analyzed to inform the current trends and identify research opportunities. To expand knowledge of how digital innovation is evolving in developing countries’ higher education institutions, this study specifically examines the existing body of information about digital innovation in higher education institutions in developing nations, as well as the research possibilities that exist to expand on this body of knowledge.